2018
DOI: 10.1177/0033294118783508
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Stress: How Should Clinicians Interpret the Total and Subscale Scores of the 21-Item Depression, Anxiety, and Stress Scales?

Abstract: The 21-item Depression, Anxiety, and Stress Scales (DASS-21) is a self-report measure that is easy to administer, quick to score, and is freely available. Widely used in diverse settings and populations, confirmatory factor analytic evidence has accumulated for a bifactor model underlying this multidimensional measure. Studies employing an exploratory bifactor approach to more closely examine its underlying structure and inter-relations of factors, however, have been scarce. This is unfortunate because confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In the current study, we used the short-form version of the Depression Anxiety Stress Scale (DASS-21, Lovibond and Lovibond, 1995) to measure the negative emotions, including depression, anxiety, and stress. The DASS-21 is an excellent tool which was conceptualized as a correlated three-factor model, and the total score of DASS-21 represents a full spectrum of negative emotional states (Lovibond and Lovibond, 1995;Chin et al, 2019; as cited in Prabhu, 2016). The buffering model of social support postulates that social support can maintain good health by decreasing the negative influence of stress on the body and mind (Gong, 1994).…”
Section: The Mediating Role Of Negative Emotions In the Relationship mentioning
confidence: 99%
“…In the current study, we used the short-form version of the Depression Anxiety Stress Scale (DASS-21, Lovibond and Lovibond, 1995) to measure the negative emotions, including depression, anxiety, and stress. The DASS-21 is an excellent tool which was conceptualized as a correlated three-factor model, and the total score of DASS-21 represents a full spectrum of negative emotional states (Lovibond and Lovibond, 1995;Chin et al, 2019; as cited in Prabhu, 2016). The buffering model of social support postulates that social support can maintain good health by decreasing the negative influence of stress on the body and mind (Gong, 1994).…”
Section: The Mediating Role Of Negative Emotions In the Relationship mentioning
confidence: 99%
“…However, Tully, Zajac, and Venning (2009) and Szabό (2010) opted for a bifactor solution with two specific factors in adolescent samples. More recently, Chin et al (2018) reported the results of both exploratory and confirmatory bifactor models on non-clinical samples supporting a bifactor solution in which only the revised Depression subscale had sufficient validity.…”
mentioning
confidence: 99%
“…Additionally, some obtained less conclusive evidence for existence of the Stress factor in their factor analytic studies (e.g., Szabό, 2010). Finally, the specificity of both the Stress and Anxiety factors (Chin, Buchanan, Ebesutani, & Young, 2018) and all three DASS-21 specific factors have been questioned recently (Osman et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are different scales used for measured these symptoms. The Depression, Anxiety and Stress Scale-21 (DASS-21) is one of them, with strong psychometric properties [ 2 , 3 ] and it is validated in Spanish [4] . Due to the increase on mental health problems it is mandatory to look for new parameters that can be used on population as screening tool.…”
mentioning
confidence: 99%